Oral health in 12- to 17-year-old athletes participating in the German Special Olympics - Bissar, Abdul-Razak; Kaschke, Imke; Schulte, Andreas G. (International journal of paediatric dentistry, 2010)
International Journal of Paediatric Dentistry 2010; 20: 451-457 Background. There is a lack of actual data regarding oral health in children and adolescents with intellectual disabilities. Aim. To evaluate the oral health in adolescents with intellectual disabilities participating in the German Special Olympics games 2008. Methods. A free voluntary dental examination was offered to the participating athletes. Dental examinations were performed according to WHO criteria by dental clinicians. In addition, information about the athletes’ oral hygiene habits was collected. Results. The number of adolescent athletes aged between 12 and 17 years who had their teeth examined was 160. On average they were 15.3 years old. Caries prevalence was 58.1% and the mean DMFT was 2.3. The mean number of fissure sealed teeth was 2.5. About half of the participants showed signs of gum inflammation. The proportion of the adolescents living at home with their parents was 88%. More than 90% of them brushed their teeth by themselves without assistance. Conclusions. Adolescents with intellectual disabilities seem to have benefited from various caries preventive measures which had been introduced during the last two decades in Germany but still have a poorer oral health than the general population. More specific prevention programmes seeking close cooperation with parents, custodians, and caretakers should be developed.